"Everyone Has to Find Themselves in the Story": Exploring Minority Group Representation in the Citizenship Curriculum in Northern Ireland and Israel. Issue 2 (2nd April 2016) - Hanna, Helen
ABSTRACT: This article explores understandings of minority group representation in citizenship education in Northern Ireland and Israel, from the point of view of students, teachers, and policy makers. It is set against the background of the minority–majority group dichotomy within societies divided along ethnonational lines, and the challenge of delivering a common citizenship curriculum to a diverse group in such a context. Starting with interpretations of international law that state that education should be culturally appropriate and flexible to the needs of a particular community, the article considers several interrelated ideas: proportional representation of the minority in educational governance, students being able to "find themselves in the story" of the curriculum, and the debate over a common versus a differentiated curriculum. Interjurisdiction comparisons allow for exploration of varied understandings of citizenship education as socialization, and of potential responses to the challenge of balancing unity and diversity in a divided or multicultural society.